2014
DOI: 10.1186/1748-717x-9-101
|View full text |Cite
|
Sign up to set email alerts
|

Significance of an increase in the Child-Pugh score after radiotherapy in patients with unresectable hepatocellular carcinoma

Abstract: BackgroundWe attempted to analyze the effects of an increase in the Child-Pugh (CP) score on the overall survival of patients with unresectable hepatocellular carcinoma (HCC) after radiotherapy (RT).MethodsFrom March 2006 to February 2012, 103 patients received RT using the TomoTherapy Hi-Art at Incheon St. Mary’s Hospital and Seoul St. Mary’s Hospital. The dose per fraction was 1.8–5 Gy, and the total dose was 40–60 Gy (median, 50 Gy). We considered an increase of at least 2 points in the CP score within 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Previous studies have attempted to identify radiographic and dosimetric predictors of liver toxicity; the percentage of liver volume receiving more than 30 Gy, percentage of lung volume receiving more than 20 Gy, pretreatment hepatopulmonary shunt fraction, and pretreatment liver cirrhosis have all been independently associated with liver toxicity following SIRT ( 36 42 ). A recent report demonstrated that a 2+ change in CP score is a clinically important indicator of decline in liver function and survival in patients with unresectable HCC who have received radiotherapy ( 15 ). This finding is supported by the survival data in our current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have attempted to identify radiographic and dosimetric predictors of liver toxicity; the percentage of liver volume receiving more than 30 Gy, percentage of lung volume receiving more than 20 Gy, pretreatment hepatopulmonary shunt fraction, and pretreatment liver cirrhosis have all been independently associated with liver toxicity following SIRT ( 36 42 ). A recent report demonstrated that a 2+ change in CP score is a clinically important indicator of decline in liver function and survival in patients with unresectable HCC who have received radiotherapy ( 15 ). This finding is supported by the survival data in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…Child-Pugh (CP) score was used to assess changes in liver function after SIRT. An increase in CP score by two or more points was deemed to be a clinically relevant indicator of decline in liver function following radiotherapy in one prior analysis ( 15 ). For data analysis purposes, changes in liver function were expressed as a binary value at 3 and 6 months post-SIRT: patients with a 2+ increase in CP score from baseline were given a 1 at each follow-up point; those with a score increase of <2 were given a 0.…”
Section: Methodsmentioning
confidence: 99%
“…Change of Child-Pugh score after RT was also evaluated. If there was change in Child-Pugh score of 2 or more points, it was considered as development of complication [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tumor response was defined as the best response in the dynamic CT scans obtained 1 month and 3 months after RT, according to the modified Response Evaluation Criteria in Solid Tumors [ 27 ]. PFS was measured from the date of RT to the date of progression or the last follow-up.…”
Section: Methodsmentioning
confidence: 99%